Autophagy inhibition promotes SNCA/alpha-synuclein release and transfer via extracellular vesicles with a hybrid autophagosome-exosome-like phenotype. Issue 1 (2nd January 2018) - Minakaki, Georgia; Menges, Stefanie; Kittel, Agnes; Emmanouilidou, Evangelia; Schaeffner, Iris; Barkovits, Katalin; Bergmann, Anna; Rockenstein, Edward; Adame, Anthony; Marxreiter, Franz; Mollenhauer, Brit; Galasko, Douglas; et al.
ABSTRACT: The autophagy-lysosome pathway (ALP) regulates intracellular homeostasis of the cytosolic protein SNCA/alpha-synuclein and is impaired in synucleinopathies, including Parkinson disease and dementia with Lewy bodies (DLB). Emerging evidence suggests that ALP influences SNCA release, but the underlying cellular mechanisms are not well understood. Several studies identified SNCA in exosome/extracellular vesicle (EV) fractions. EVs are generated in the multivesicular body compartment and either released upon its fusion with the plasma membrane, or cleared via the ALP. We therefore hypothesized that inhibiting ALP clearance 1) enhances SNCA release via EVs by increasing extracellular shuttling of multivesicular body contents, 2) alters EV biochemical profile, and 3) promotes SNCA cell-to-cell transfer. Indeed, ALP inhibition increased the ratio of extra- to intracellular SNCA and upregulated SNCA association with EVs in neuronal cells. Ultrastructural analysis revealed a widespread, fused multivesicular body-autophagosome compartment. Biochemical characterization revealed the presence of autophagosome-related proteins, such as LC3-II and SQSTM1. This distinct "autophagosome-exosome-like" profile was also identified in human cerebrospinal fluid (CSF) EVs. After a single intracortical injection of SNCA-containing EVs derived from CSF into mice, human SNCA colocalized with endosome and neuronal markers. Prominent SNCA immunoreactivity and a higher number of neuronal SNCA inclusions were observed after DLB patient CSF EV injections. In summary, this study provides compelling evidence that a) ALP inhibition increases SNCA in neuronal EVs, b) distinct ALP components are present in EVs, and c) CSF EVs transfer SNCA from cell to cell in vivo. Thus, macroautophagy/autophagy may regulate EV protein composition and consequently progression in synucleinopathies.